Semiotic Analysis of Roland Barthes on Wardah Advertisement Version “I Face of Indonesia” - Nurhasanah Purba; Khairunnisa Tambunan (Britain International for Academic Research (BIAR-Publisher), 2021)
This study aims to represent the meaning of the advertisement using Barthes' semiotic sign map and to describe the meaning contained in the wardah advertisement version of